Chemically modified hCFTR mRNAs recuperate lung function in a mouse model of cystic fibrosis. Issue 1 (December 2018) - Haque, A.; Dewerth, Alexander; Antony, Justin; Riethmüller, Joachim; Schweizer, Georg; Weinmann, Petra; Latifi, Ngadhnjim; Yasar, Hanzey; Pedemonte, Nicoletta; Sondo, Elvira; Weidensee, Brian; Ralhan, Anjali; et al.
Abstract Gene therapy has always been a promising therapeutic approach for Cystic Fibrosis (CF). However, numerous trials using DNA or viral vectors encoding the correct protein resulted in a general low efficacy. In the last years, chemically modified messenger RNA (cmRNA) has been proven to be a highly potent, pulmonary drug. Consequently, we first explored the expression, function and immunogenicity of human (h)CFTR encoded by cmRNAhCFTR in vitro andex vivo, quantified the expression by flow cytometry, determined its function using a YFP based assay and checked the immune response in human whole blood. Similarly, we examined the function of cmRNAhCFTR in vivo after intratracheal (i.t.) or intravenous (i.v.) injection of the assembled cmRNAhCFTR together with Chitosan-coated PLGA (poly-D, L-lactide-co-glycolide 75:25 (Resomer RG 752 H)) nanoparticles (NPs) by FlexiVent. The amount of expression of human hCFTR encoded by cmRNAhCFTR was quantified by hCFTR ELISA, and cmRNAhCFTR values were assessed by RT-qPCR. Thereby, we observed a significant improvement of lung function, especially in regards to FEV0.1, suggesting NP-cmRNAhCFTR as promising therapeutic option for CF patients independent of theirCFTR genotype.